Effect of Nutmeg (Myristica fragrans Houtt.) Seed Essential Oil Addition to Chitosan Edible Coating on The Quality of Broiler Chicken Fillet during Cold Storage - Windi Atmaka; Siti Khodijah Putri Wibisono; Siswanti -; Esti Widowati (Universitas Sebelas Maret (UNS), 2024)
Chicken is a highly demanded meat due to its high nutritional value and affordability. However, chicken meat has a relatively short shelf life and is susceptible to damage during storage. One way to preserve the quality of chicken meat is to use an edible coating. This study was conducted to determine the effect of adding nutmeg (Myristica fragrans Houtt.) seed essential oil at a specified concentration in chitosan edible coating on the quality of broiler meat fillets during 12 days of storage at cold temperatures. The test parameters used as a reference for the quality of broiler meat fillets include TPC, TVB, TBA, pH, and cooking loss tests. The experimental design in this study was a completely randomized design (CRD) with a factor of variation in the concentration of nutmeg essential oil (0%, 0,25%, 0,5%, 0,75%, and 1%). The data obtained were analyzed using one-way ANOVA. If there is a difference, it is continued with the Duncan Multiple Range Test (DMRT) to determine whether there is a difference in each sample at a significance level of α = 0,05. Then, the potency test was conducted to determine the sample with the best concentration of nutmeg essential oil. The results showed that 1% concentration of nutmeg essential oil showed the best results in maintaining the quality of chicken fillet during cold storage (4oC), based on the efficacy test. There was a difference between the quality of chicken fillet meat in the best concentration sample (addition of 1% nutmeg seed essential oil) and chicken meat samples without coating on the parameters of cooking loss, pH, TBA, and TPC.